Economic growth model with delay - Barzdžiukas, Raimondas; Eitkevičiūtė, Rasa; Švitra, Osvaldas (Lietuvos matematikos rinkinys, 2012)
In this article the authors analyzed nonlinear model with delay of production growth. In the nonlinear analysis were obtained the results are compared with real date.
Keywords: mathematical modeling of the production process; differential equations; stable periodic solution